Gone viral? Heard the buzz? A guide for public health practitioners and researchers on how Web 2.0 can subvert advertising restrictions and spread health information. Issue 9 (13th August 2008) - Freeman, B; Chapman, S
Abstract : Many nations have banned or curtailed advertising of potentially harmful products to protect public health, particularly in the area of chronic disease control. The growth in Internet-based marketing techniques is subverting these advertising regulations. Explosive rises in use of social networking and user-generated content websites is further fuelling product promotion through electronic media. In contrast, there is a very limited body of public health research on these "new media„ advertising methods. This paper provides an overview of these advertising methods and details examples relevant to chronic disease control. There is a vast untapped potential for health practitioners and researchers to exploit these same media for health promotion.